Management and Evaluation within the Plano Plurianual : Institutionalization without Impact? - World Bank (Washington, DC, 2013)
This report was prepared in response to the request from the Government of Brazil to evaluate the experiencia de Avaliacao do Plano Plurianual (PPA's) evaluation system and propose ways it could be strengthened. In our understanding, the genesis of the PPA as an instrument of government planning and management and its philosophy was circa 1999. It was then that the decision was made to apply a particular planning model piloted with a set of priority projects (Brazil em Acao) in the 1996-99 PPA to the entire set of government activities in the PPA 2000-03. The current state of the PPA reflects a series of evolutionary changes since then, with the improvements in its evaluation framework being one of them. Because of this origin, understanding and evaluating the PPA evaluation system will require placing it in the context of the evolution and the effectiveness of the whole PPA, as envisioned in its original model and its subsequent adaptations. The point of departure is the observation that the primary challenge is to make the PPA effective as an instrument to make the federal administration more performance oriented. Improvements to the evaluation system as such, though welcome and needed, should be a secondary objective for the government, as this is only a limited part of the whole endeavor.